Native Kaempferia galanga L. in Vietnam: Biological Characteristics and Potential Applications for Human Health Care - Do Thi Dinh; Le Minh Ha; Bui Thi Thuy Luyen (Tecno Scientifica Publishing, 2026)
Kaempferia galanga is an important medicinal and economic herb of the Zingiberaceae family with significant potential for healthcare applications in Vietnam. This review was the first comprehensive synthesis focusing specifically on Vietnamese evidence regarding the botanical characteristics, cultivation practices, genetic resources, phytochemical composition, pharmacological activities, and traditional medicinal uses of this species. Available studies indicated that K. galanga was widely cultivated across Vietnam and demonstrated promising agronomic performance, with essential oil yields of 4.2–4.43% under optimized cultivation conditions and efficient in vitro propagation achieving 5.03 shoots per explant. Phytochemical investigations revealed a rich diversity of bioactive compounds, including ethyl p-methoxycinnamate, terpenoids, phenolics, flavonoids, and diarylheptanoids, which underpinned multiple biological activities. Experimental studies conducted in Vietnam demonstrated antioxidant, antifungal, anti-inflammatory, and uric acid-lowering effects, supporting its traditional use in treating digestive disorders, musculoskeletal pain, inflammatory conditions, and respiratory ailments. Given its local availability and pharmacological potential, K. galanga represented a promising medicinal resource for evidence-based herbal therapeutics and community healthcare in Vietnam. However, important gaps remained regarding chemotype standardization, clinical validation, and sustainable cultivation strategies. This review provided a scientific foundation for future pharmaceutical development, conservation, and effective healthcare utilization of K. galanga in Vietnam.